2006
DOI: 10.1159/000093062
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size of Hydroxyapatite Granules Calcified from Red Algae Affects the Osteogenic Potential of Human Mesenchymal Stem Cells in vitro

Abstract: Hydroxyapatite (HA) microparticles as a carrier in an injectable tissue-engineered bone filler are considered promising candidates for the treatment of small bone defects in the craniomaxillofacial region. HA granules calcified from red algae, varying in size, were evaluated in vitro for their suitability to be used as a carrier for human mesenchymal stem cells (hMSCs). Three groups of granules were produced in grain sizes of 10–100, 200–500 and 600–1,000 µm. After seeding and culturing hMSCs under osteogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 78 publications
3
23
0
Order By: Relevance
“…At day 7, no significant difference was found between Bone Save ® and Pro-Osteon TM at day 7, despite having a similar chemical composition (Table 2). This indicates that particle size has a significant influence on cell behaviour in vitro and supports work by Weiβ enböck et al, who found that particle size and substrate geometry significantly influenced cell signaling [30].…”
Section: Biological Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…At day 7, no significant difference was found between Bone Save ® and Pro-Osteon TM at day 7, despite having a similar chemical composition (Table 2). This indicates that particle size has a significant influence on cell behaviour in vitro and supports work by Weiβ enböck et al, who found that particle size and substrate geometry significantly influenced cell signaling [30].…”
Section: Biological Characterizationsupporting
confidence: 88%
“…The main benefit of coral-derived bone void fillers over synthetic alternatives is their bioresorption capacity [25,26]. Recently, other sustainable calcified marine structures and organisms, such as mussels [27, cuttlefish bone [28] and algae [26,29,30] have been investigated for bone void filler applications.…”
Section: Tm and Biocoralmentioning
confidence: 99%
“…8 A variety of in vitro and in vivo studies have been conducted to quantify the impact of this factor on the progress and outcome of bone regeneration, but no definitive conclusions have thus far been reached. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Following previous studies conducted by our group analyzing tissue reactions to bone substitute materials with a special focus on their chemical composition and physical characteristics, the present study investigates the influence of granule size of a biphasic bone substitute material. In this investigation 2 granule sizes of BoneCeramic Ò (500-1000 mm and 400-700 mm) were tested with respect to the tissue reaction in a subcutaneous implantation model in Wistar rats over a 60 day period.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to culture the cells on the inserts with the subsequent risk of escape of cells through the net of the inserts instead of culturing directly on the wells, as performed in similar other published experiments (Hosseinkhani et al, 2005;Turhani et al, 2005;Shih et al, 2006;Weissenböeck et al, 2006;Zhou et al, 2007;Bjerre et al, 2008;Heo et al, 2009;Huang et al, 2009;Shi et al, 2009;Stiehler et al, 2009). This makes change of the medium Fig.…”
Section: Discussionmentioning
confidence: 99%